Myma / Alif Darwisy Mohd Fauzi ...[et al.] - Mohd Fauzi, Alif Darwisy; Azizi, Mukhriz; Mohd Sham, Intan Nur Mawaddah; Mohd Zaki, Fatin Nabila (2023)
This business is based on a partnership where it consists of four members in which they hold important positions in the company such as General Manage which also acts as an Administration Manager, Marketing Manager, Operational Manager, and Financial Manager. The name of our company is ‘MyMa’. It comes from the short abbreviation of the words ‘my mama’ or the literal meaning is “my mother”. Babies usually have ‘mama’ their first spoken word as they mostly interact with the mothers when they were born as mothers have their confinement period after giving birth. The word ‘my’ symbolizes the baby looking at their mothers and imprinting their moms as their own. We provide our customers with Meal Ready to Eat or also known as MRE that is perfect for mothers in confinement called MREC. Mothers nowadays have their own jobs and even though they have their maternity leave provided, an emergency may happen at the workplace, so she needs to work from home. Moreover, if a family can’t afford to pay for confinement services, the mother may struggle to cook whilst taking care of the baby. MREC is the perfect solution as it is easy to make and only takes 5 minutes to cook. This will ease the burden of mothers in confinement and provide them with the nutrients that they need. MyMa will be starting at Bandar Baru Uda, Johor Bahru 81200, Johor. We chose to start our company here in Bandar Baru Uda, Johor Bahru 81200, Johor because it is near to towns and has a lot of housing areas where we can target future and existing families. Our business will commence operation on 2nd February 2023. MyMa will ease the burden of modern mothers in the near future.